Pengaruh Self-Efficacy dan Motivasi Belajar Dengan Kemampuan Pemecahan Masalah Pada Mata Kuliah Pendidikan Kewarganegaraan - Sari, Nurullita; Therreshia, Annisha; Rahmah, Siti (CV. Kurnia Grup, 2024)
This study investigates the relationship between self-efficacy and learning motivation with problem-solving skills in the Citizenship Education course among students in the PPKn program at Pamulang University for the 2023/2024 academic year. Citizenship Education plays a crucial role in shaping students’ understanding of citizenship values, rights, obligations, and responsibilities. Problem-solving skills are seen as key to applying these values. The study focuses on psychological factors influencing problem-solving ability, specifically self-efficacy (belief in one’s capability to handle tasks) and learning motivation (internal drive to learn). The research uses a survey method with questionnaires assessing self-efficacy, learning motivation, and problem-solving skills among PPKn students. The collected data will be analyzed to identify relationships between the variables. This study aims to provide insights for developing learning strategies that support students' problem-solving skills, preparing them to become critical and active citizens.